1999
DOI: 10.1891/1061-3749.7.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Instrument to Measure Community Acceptance of Nurse Practictioners and Physician Assistants

Abstract: The purpose of this study was to identify the significant dimensions of the concept of community acceptance of nurse practitioners/physician’s assistants and to construct areliable and valid instrument which would reflect these dimensions. The methodological approach included: conceptualization of categories, development of items for each category, development of the tool, administration of the tool, and psychometric analysis of results. Community input through focus-group interviews and post-administration qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…An exhaustive review of the literature indicated that no existing instrument entirely and satisfactorily demonstrated promise or pertinence to the specific objective of the study. Therefore, the Nurse Practitioner Satisfaction Survey (NPSS), a 5‐point Likert‐type survey, was created specifically for the purposes of this study from a compilation of numerous satisfaction scales reviewed, a review of related literature, and professional opinion (Alexander, 2001; Baer, et al, 1999; Bear & Bowers, 1998; Cole, Mackey, & Lindenberg, 1999; Courtney & Rice, 1997; DiTomasso &Willard, 1991; Marsh, 1999). The NPSS (Agosta, 2005) is composed of 28 Likert‐type items compiled with the intent of including concepts viewed as relevant and instrumental in influencing overall patient satisfaction with care.…”
Section: Methodsmentioning
confidence: 99%
“…An exhaustive review of the literature indicated that no existing instrument entirely and satisfactorily demonstrated promise or pertinence to the specific objective of the study. Therefore, the Nurse Practitioner Satisfaction Survey (NPSS), a 5‐point Likert‐type survey, was created specifically for the purposes of this study from a compilation of numerous satisfaction scales reviewed, a review of related literature, and professional opinion (Alexander, 2001; Baer, et al, 1999; Bear & Bowers, 1998; Cole, Mackey, & Lindenberg, 1999; Courtney & Rice, 1997; DiTomasso &Willard, 1991; Marsh, 1999). The NPSS (Agosta, 2005) is composed of 28 Likert‐type items compiled with the intent of including concepts viewed as relevant and instrumental in influencing overall patient satisfaction with care.…”
Section: Methodsmentioning
confidence: 99%
“…In the first-order analysis, items specific to trust and access loaded on three distinct factors (Baer et al, 1999); however, in the second-order analysis these three factors converged into a single factor. The methodological question raised by this analysis is: ''Does the clustering of the trust and access related factors correspond with the elimination of difficulty factors that might occur when using factor analysis on dichotomous data?''…”
Section: Discussionmentioning
confidence: 86%
“…This instrument was developed based on focus group analysis, extensive literature review, and expert opinion. Through this process, items for the instrument were constructed to reflect four underlying concepts of acceptance: trust, knowledge, competence, and access (Baer et al, 1999). The 40 items that comprised this instrument assessed community acceptance of NPs and PAs in a rural setting.…”
Section: Methods and Resultsmentioning
confidence: 99%
See 2 more Smart Citations